Literature Study of the Impact of Regional Financial Management, Accountability, and Transparency on Regional Government Financial Performance - Sipahutar, Bela Putri Saqina; Rahwani, Diba Ameilia; Zebua, Dwi Fadhillah Apriliana (Lembaga Riset Mutiara Akbar (LARISMA), 2024)
The purpose of this study is to examine the impact of regional financial management, accountability, and transparency on the financial performance of local governments. This study was conducted through a qualitative method with a literature study approach, where data was collected from various books, journals, and online sources. The results of the study indicate that good regional financial governance, accompanied by clear accountability and effective transparency, has a significant and positive impact on the financial performance of local governments. This finding emphasizes the importance of a comprehensive approach to achieving optimal financial performance at the local government level.